2013
DOI: 10.1590/s1983-14472013000400005
|View full text |Cite
|
Sign up to set email alerts
|

Análise conceitual de autogestão do indivíduo hipertenso

Abstract: This research aimed to analyze the concept of self-management of hypertensive individuals. Theoretical and documentary study based on Walker and Avant's conceptual analysis by means of the Scientific Electronic Library Brazil and the Medical Literature Analysis and Retrieval System Online in the Coordination for Higher Education Personnel Development (CAPES, in Portuguese) and the National Library of Medicine websites. Fourteen (14) articles and one (1) thesis were selected and reviewed, in Portuguese and Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
1
9
0
5
Order By: Relevance
“…Hypertensive individuals who self-manage their disease and have positive beliefs maintain healthy lifestyles. The role of healthcare professionals in the treatment of hypertension is to seek the knowledge that patients need and to mediate the needed changes, thereby contributing to behavioural changes (Balduino et al 2013).…”
Section: Experiencing Attitudes and Actions In The Control And Treatmmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypertensive individuals who self-manage their disease and have positive beliefs maintain healthy lifestyles. The role of healthcare professionals in the treatment of hypertension is to seek the knowledge that patients need and to mediate the needed changes, thereby contributing to behavioural changes (Balduino et al 2013).…”
Section: Experiencing Attitudes and Actions In The Control And Treatmmentioning
confidence: 99%
“…Hypertensive patients need both individual educational activities and counselling with healthcare professionals to adopt healthy lifestyle changes and comprehend the nature of self-management of their health care (Balduino et al 2013). One study in the USA found that shared clinical consultations and professional visits were regarded as an innovation that primarily allowed improvements in access to care, costs and results of disease management and also provided care to patients in a manner that was more sensitive to their needs.…”
Section: Experiencing Attitudes and Actions In The Control And Treatmmentioning
confidence: 99%
See 1 more Smart Citation
“…O usuário do serviço de saúde deve ser capacitado para o autocuidado, que é dependente de padrões culturais, familiares e sociais. O conceito de autogestão é um processo dinâmico e ativo, requerendo conhecimento, atitude, disciplina, determinação, comprometimento, autorregulação, empoderamento e autoeficácia para gerir a doença, na busca de um viver saudável 21 . Todos esses fatores devem ser levados em conta nas abordagens educativas em saúde.…”
Section: Discussionunclassified
“…Thus, it is emphasized that, for successful control of systemic arterial hypertension, it is necessary to practice selfcare by the patient. This is defined as the realization of performing activities that individuals play to their benefit to maintain life, health, and welfare (4) . When self-care is effectively performed, it helps to maintain the structural and functional integrity, contributing to human development (5) .…”
Section: Introductionmentioning
confidence: 99%